2009
DOI: 10.1371/journal.pbio.1000228
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Lyso-Phospholipids by Human Natural Killer T Lymphocytes

Abstract: By identifying the lipid LPC as an endogenous antigen, recognized by the invariant subset of human NKT cells, this study establishes a novel link between these immunoregulatory cells and an inflammatory lipid mediator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
212
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(220 citation statements)
references
References 50 publications
3
212
0
1
Order By: Relevance
“…Similar to microbial lipid CD1d antigens, the majority of the endogenous antigens identified belong to two lipid classes, glycerolbased phospholipids and glycosphingolipids (GSL). Phosphatidylinositol (PI), phosphatidylcholine (PC), phosphatidylethanolamine (PE), and lyso-PC have been shown to stimulate a small subset of NKT hybridomas in vitro (20)(21)(22). A number of mammalian GSL have been identified as NKT cell antigens.…”
mentioning
confidence: 99%
“…Similar to microbial lipid CD1d antigens, the majority of the endogenous antigens identified belong to two lipid classes, glycerolbased phospholipids and glycosphingolipids (GSL). Phosphatidylinositol (PI), phosphatidylcholine (PC), phosphatidylethanolamine (PE), and lyso-PC have been shown to stimulate a small subset of NKT hybridomas in vitro (20)(21)(22). A number of mammalian GSL have been identified as NKT cell antigens.…”
mentioning
confidence: 99%
“…Actual measurements of mouse CD1d complexes formed in cells first suggested that cellular ligands were dominated by one class of phosphatidylinositol-containing molecule (2), and CD1b was reported to bind PC in a selective way (27). However, subsequent study of mouse and human CD1d detected several types of phospho-and sphingolipid ligands (12)(13)(14), suggesting greater diversity of lipid ligands for CD1d. Using cellular CD1 proteins lacking endosomal targeting motifs and captured under two different conditions that avoid the acid-mediated unloading effects, our comparative lipidomics approach provides evidence for substantial diversity of CD1 ligands for each of the four human CD1 proteins, detecting hundreds of molecular features whose retention times vary greatly.…”
Section: Discussionmentioning
confidence: 99%
“…This expectation is supported by experiments that detect self-diacylglycerols, monoacylglycerols, and sphingolipids eluted from CD1 proteins that have ER retention signals or lack endosomal recycling motifs (2,12,13). Some of these endogenous lipids activate T cells, so are true autoantigens (14). Others are more likely nonantigenic place-holding lipids that provide a hydrophobic substrate for the initial folding reactions and serve a groove-blocking function until antigenic exogenous lipids are encountered in acidic endosomes.…”
mentioning
confidence: 92%
“…The recombinant human CD1d molecules used in our cell-free assays are purified from HEK293T cells and are loaded with a spectrum of cell lipids derived from the ER, Golgi, and secretory compartment (55), some of which are reported to be antigenic for human iNKT cells (56). Therefore, the capacity of lipid-bound saposin B to load these recombinant CD1d molecules also implied its ability to promote lipid exchange.…”
Section: Discussionmentioning
confidence: 99%